Medications adherence level and its associated factors among hypertensive patients at a major referral hospital, in Riyadh, KSA - Shaik, Shaffi Ahamed; Alsuwailem, Abeer; Alhargan, Afnan; Alswailem, Asma; Alshiha, Dania; AlGhalib, Hanan; Alamri, Raghdah; Al-Hazmi, Ali (Asian Journal of Medical Sciences, 2016)
Aims and Objectives: To quantify the level of medications adherence among hypertensive patients and to identify factors of poor adherence. Materials and Methods: A cross sectional study was conducted during October 2013 to March 2014 in King Khalid University Hospital, Riyadh, KSA. Self-administrative questionnaires were used among 310 randomly selected hypertensive patients. Morisky adherence questionnaire was used to quantify adherence level of medications. Adherence scores were categorized as poor and high adherence. Bi-variate and multivariate analysis were used to identity factors associated with poor adherence. Results: Out of 287 patients who had responded, 124(44%) were of less than 50 years of age. Prevalence of poor adherence to medications was 55%. Age, educational status, monthly income, time of diagnosis, self-perception of health status, regular checkup at clinics, & regular blood pressure checkup were significantly associated with ‘level of adherence (poor and high) to medications. The independent associated factors of poor adherence were: age (<50 years): 2.30 (95% confidence interval(CI): 1.29,4.10), monthly income (<5000 Saudi Riyals): 6.58(1.67,25.97), self-perception of health status (uncontrolled): 2.66 (1.20,5.90), and regular checkup at clinics (No): 5.57(2.83,10.97). Conclusion: Level of adherence was low among hypertensive patients. Associated factors of poor adherence could be used to identity patients for counselling in improving level of adherence to medications. Asian Journal of Medical Sciences Vol.7(4) 2016 24-30